The Detection of Genes Encoding Enzyme Fructosyltransferase The Exopolysaccharide (EPS) Produce Potential Probiotic Candidates For Breast Milk (ASI) - Afifah Nurul Falih; Nosa Septiana Anindita; Arif Bimantara; Annisa Khumaira (Universitas 'Aisyiyah Yogyakarta, 2022)
Bacteria is one of the microorganisms that we can easily find in nature. Bacteria can be classified into benefical bacteria and harmful bacteria. One of the bacteria classified as benefical bacteria is lactic acid bacteria (LAB). One of the bacteria included in LAB is probiotic bacteria. Probiotic bacteria can be isolated from several sources, one of which is breast milk. The functionality of probiotics is seen by the production of exopolysaccharides (EPS). EPS is produced through the expression of the fructosyltransferase (ftf) gene. The samples used in this study were 16 isolates of candidate probiotic bacteria from breast milk. The stages of this research included reculture of probiotic isolates, isolation of bacterial genomic DNA, amplification of isolates with 16s rRNA primers, amplification of isolates with primary lactic acid bacteria (LAB) and amplification of isolates with specific primers of ftf gene. The results showed that 10 of 16 probiotic bacterial isolates had the ftf gene indicated by the presence of DNA bands on the electrophoregram with a size 58 bp.